ANALISIS UNJUK KERJA PLTD-G 40 KW BERBAHAN BAKAR MINYAK DIESEL DAN PELET BIOMASSA (STUDI KASUS DI PT INDONESIA POWER BALI) - Yohana Fransisca Sarumpaet; I Nyoman Satya Kumara; Wayan Gede Ariastina (Program Studi Teknik Elektro UNUD, 2020)
Fossil-fueled power plants are still the world’s backbone in terms of electricitygeneration, including in Indonesia. This will continue to increase due to the high demand ofelectricity. Meanwhile, the amount of fossil fuels is limited and fossil fuel creates exhaustemissions. Therefore, it is required to look for clean and renewable electricity generationmethods. The development of Diesel Gasifier Power Plant carried out by PT Indonesia PowerBali aims to reduce the use of diesel by using syngas obtained from gasification of biomasspellets. This study analyzes the performance of the Diesel Gasifier Power Plant at PT IndonesiaPower Bali. The results show that the use of syngas reduces the use of diesel, this is indicatedby the fuel consumption ratio between diesel and syngas, which is 56% diesel and 44% syngas.The results also show that the Diesel Gasifier Power Plant has an efficiency of 63% and acapacity factor of 58%.